The effect of antibiotic therapy on clinical outcome in patients hospitalized with moderate COVID-19 disease: a prospective multi-center cohort study - Friedrichs, Anette; Wenz, Roman; Pape, Daniel; Appel, Katharina; Bahmer, Thomas; Becker, Karsten; Bercker, Sven; Blaschke, Sabine; Braunsteiner, Josephine; Butzmann, Jana; Dahl, Edgar; Erber, Johanna; et al. (Infection, 2025)
Purpose The benefit of antibiotic treatment (ABT) for patients with moderate COVID-19 is unclear and overtreatment poses the risk of adverse effects such as Clostridioides difficile infection and antibiotic resistance. This multi-center study compares health status improvement between patients with and without ABT at hospital admission. Methods Between March 2020 and May 2023, hospitalized adults with confirmed SARS-CoV-2 infection were recruited from the German National Pandemic Cohort Network (NAPKON), which includes patients from various hospitals across Germany. The study population included patients with moderate or severe COVID-19 at baseline. The primary objective was to compare health improvement or decline after two weeks between patients who received ABT at baseline and those who did not in the moderate COVID-19 population. The statistical analysis adjusted for confounders such as gender, age, vaccination status, clinical condition, and comorbidities. The severe COVID-19 population was investigated as a secondary objective. Results A total of 1,317 patients (median age 59 years; 38% women) were eligible for analysis, of whom 1,149 had moderate and 168 severe COVID-19 disease. ABT for pneumonia was administered to 467 patients with moderate and 117 with severe COVID-19. ABT at baseline was significantly associated with a higher deterioration rate after two weeks in patients with moderate COVID-19 (ABT: 292 improvement, 61 deterioration; no ABT: 429 improvement, 14 deterioration). A similar result was obtained in the multiple regression analysis where an odds ratio of 5.00 (95% confidence interval: 2.50 - 10.93) for ABT was observed. Conclusion We found no benefit of antibiotic therapy in patients with moderate COVID-19. Use of ABT was associated with a higher likelihood of clinical deterioration. Graphical abstract